Pengaruh Religiositas dan Perfeksionisme terhadap Kecemasan Mahasiswa dalam Menyusun Skripsi - Eko Sujadi; Yuserizal Bustami (Prodi Bimbingan dan Konseling Islam, 2023)
Academic challenges faced by students can vary and have an impact on their psychological well-being. One of the demands that can lead to academic anxiety is the preparation of a thesis. Limited time, parental pressure, costs, understanding of the research topic, and interactions with the supervising professors can all contribute to these issues. The purpose of this study is to describe the anxiety experienced by students in preparing their theses and to analyze the influence of religiosity and perfectionism on this anxiety. We employed an online survey research design. Over a period of approximately three weeks, 131 students from the Faculty of Islamic Economics and Business at a university in the Jambi Province, Indonesia, participated in completing the Academic Anxiety Scale, Religiosity among Muslim Scale, and Frost Multidimensional Perfectionism Scale (FMPS). The research findings revealed that students' anxiety levels during thesis preparation fell under the moderate category. Furthermore, a significant influence of religiosity and perfectionism on the experienced anxiety was identified. This indicates that strong and active religiosity may be associated with lower levels of anxiety. These findings have important implications for prevention and alleviation programs targeting academic anxiety experienced by students. Counseling services within universities need to be maximized to identify specific factors that contribute to these issues, along with implementing corresponding intervention programs. Furthermore, the academic guidance process provided by supervising professors can also be utilized as one of the prevention strategies.